2008
DOI: 10.1590/s0100-06832008000600034
|View full text |Cite
|
Sign up to set email alerts
|

Ciclagem de nutrientes via precipitação pluvial total, interna e escoamento pelo tronco em sistema agroflorestal com Gliricidia sepium

Abstract: (3) RESUMO A deposição de nutrientes contidos na água de chuva que passa pela copa das árvores e que escoa pelo tronco até o solo pode constituir uma via importante da ciclagem biogeoquímica em sistemas agroflorestais de baixo uso de insumos externos. Todavia, não há informação disponível sobre esses processos em agroecossistemas da região semi-árida do Nordeste brasileiro. O presente trabalho foi conduzido em um sistema agroflorestal de cultivo em aléias, com gliricídia e milho, em Esperança, PB, e teve como … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…33 Thus, the physical impact of raindrops was attenuated, and the stability of aggregates was maintained, which reduced the amount of transported materials and the soil nutrient losses under the canopy, especially of minerals with low mobility in the soil, including P, whose primary loss process is leaching. 34 Furthermore, the increased nutrient concentrations may have resulted from the decomposition of leaves accumulated under the canopy, exudation from roots or from stemflow, which is the transport of leaf and trunk nutrients, especially K + , by rainwater, 1,35,36 therefore, the nutrients remain concentrated near the trunk base. 2 Cordia oncocalyx trees showed differences in the nutrient concentrations of sun leaves between the rainy months (RM) and 50 dar (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…33 Thus, the physical impact of raindrops was attenuated, and the stability of aggregates was maintained, which reduced the amount of transported materials and the soil nutrient losses under the canopy, especially of minerals with low mobility in the soil, including P, whose primary loss process is leaching. 34 Furthermore, the increased nutrient concentrations may have resulted from the decomposition of leaves accumulated under the canopy, exudation from roots or from stemflow, which is the transport of leaf and trunk nutrients, especially K + , by rainwater, 1,35,36 therefore, the nutrients remain concentrated near the trunk base. 2 Cordia oncocalyx trees showed differences in the nutrient concentrations of sun leaves between the rainy months (RM) and 50 dar (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to the results obtained in the present study, the mentioned authors observed a comparable value for RF events over 50 mm (41% of accumulated depth), indicating that, although less frequent, these events have great influence on the water balance in forest ecosystems, regardless of the region where they are located. Albuquerque and Costa (2012) highlight that events with small RF depths are also important for the forest water balance, mainly for the plant-soil system, since they regulate the water flow to the soil and to the root system, with different volumes and compositions among the hydrological processes (PEREZ-MARIN;MENEZES, 2008). Considering that rainfall events in the region are characterized by small depths, it is expected that TF in the studied region presents high spatial variability due to the incomplete saturation of the forest canopy in this type of event.…”
Section: Discussionmentioning
confidence: 99%
“…Perez-Marin e Menezes (2008) puderam deduzir que, devido a interceptação de uma quantidade significativa de água pelas copas, há menos escoamento superficial e menor suprimento de água para o lençol freático. Porém, estes mecanismos levam a uma menor perda do solo, nutrientes e água por lixiviação, erosão e escoamento subsuperficial.…”
Section: Mata Atlântica E O Ciclo Hidrológicounclassified